Analysis of Romanian Bacteroides isolates for antibiotic resistance levels and the corresponding antibiotic resistance genes. (February 2015) - Székely, Edit; Eitel, Zsuzsa; Molnár, Szabolcs; Szász, Izabella Éva; Bilca, Doina; Sóki, József
Abstract: As part of an ESCMID Study Group on Anaerobic Infections (ESGAI) project, a study was conducted to measure the antibiotic susceptibilities and corresponding gene contents of 53 Bacteroides fragilis group strains isolated in Romania. The antibiotic resistance data was comparable with the data found for other East-European countries. Here, no resistant isolate was found for imipenem, metronidazole and tigecycline. An increasing role of the cepA, cfxA and cfiA genes was observed in their corresponding antibiotic resistances. Moreover, no isolate was found that harbored the cfiA gene with a possible activating IS element. Clindamycin resistance was low, similarly to that the rate for the ermF gene. However, we did find some isolates with nimB, ermB, msrSA, linA, satG, tetX, tetM and bexA genes. This study was the first to provide antibiotic resistance data for clinical Bacteroides strains from Romania. Highlights: We supply antibiotic susceptibility data for Romanian Bacteroides strains. The antibiotic susceptibility data were comparable to other European countries. Detection of the corresponding antibiotic resistance genes gave similar patterns too. However, some specificity, like the relative lack of ermF gene was also found.